Numerical studies of installation and extraction processes of jack-up ships - Qiu, Gang; Grabe, Jürgen; Kukolka, Nikolai; Vollstedt, Hans Werner (ASME, 2011)
New Jack-up ships are built to transport offshore wind turbines from harbor and assemble them with the help of cranes on the ship at the site of installation. Every ship has four stilts, which can be lowered to seabed and jack the ship up. However, penetration and extraction the stilts at the harbor area could jeopardize the existing quay wall construction. In this paper two conceptual designs of foundations, which are used to improve the strength of the seabed in front of the quay wall, are investigated using numerical methods. Through soil exchange in openended cylinder or bucket foundation the strength of the seabed should be improved so that jack-up ships can dock directly at the quay wall and lower the stilts into the foundations. Three dimensional finite element analysis using a coupled Eulerian- Lagrangian method (CEL) are carried out to simulate penetration and extraction process. A hypoplastic constitutive model and the Mohr-Coulomb constitutive model are used to describe the filling. The studies of influences of geometry of foundations as well as the soil parameters on the bearing capacity of stilts and failure mechanism in foundations are carried out as the design basis of the foundations.